Peran Orang Tua dalam Pembelajaran Daring Siswa Madrasah Ibtidaiyah Selama Transisi Pasca Pandemi (Lembaga Pengembangan Kinerja Dosen, 2025)
The transformation of the post-pandemic education system has crystallized online learning as a permanent component, with parents assuming an unprecedented instructional role at the elementary level, particularly at Madrasah Ibtidaiyah (MI). This qualitative case study aims to analyze in depth the dynamics and implications of the role of these parents during the transition period. Data was collected through in-depth interviews with parents, students, and teachers from two MIs in Blora, enriched by observation and analysis of communication documents. The findings of the study reveal three crucial things: first, there is a transformation of the role of parents into